Interdisciplinary Approach in The Development of Modern Islamic Studies - Rifai, Masyhuri; Trisnawati, Ira; Nur Aflaha, Ardhina (Universitas Islam Negeri Alauddin, 2025)
The study of modern Islam faces social, cultural, political, and scientific complexities that cannot be addressed solely through a normative-theological approach. This study aims to explore the urgency, implementation, and challenges of an interdisciplinary approach in the development of modern Islamic studies. The method used is a literature study by examining academic works on the integration of Islamic sciences with social sciences, humanities, and science. The results show that an interdisciplinary approach broadens the comprehensive understanding of Islam, both in the study of tafsir, hadith, and fiqh, as well as in the curriculum practices at PTKIN and Islamic-based schools. The challenges that arise include resistance from conservative circles, limited academic resources, and methodological conflicts between disciplines. The novelty of this research lies in the synthesis of Nissani's interdisciplinary theory, Amin Abdullah's integration-interconnection paradigm, and Miller's concept of epistemic collaboration, which emphasises that interdisciplinarity is not merely a methodological choice but a strategic paradigm in building more dynamic, inclusive, and solution-oriented Islamic studies. Studi Islam modern menghadapi kompleksitas sosial, budaya, politik, dan ilmu pengetahuan kontemporer yang tidak dapat dijawab hanya dengan pendekatan normatif-teologis. Penelitian ini bertujuan mengeksplorasi urgensi, implementasi, dan tantangan pendekatan interdisipliner dalam pengembangan studi Islam modern. Metode yang digunakan adalah studi literatur dengan menelaah karya-karya akademik mengenai integrasi ilmu keislaman dengan ilmu sosial, humaniora, dan sains. Hasil penelitian menunjukkan bahwa pendekatan interdisipliner memperluas pemahaman Islam secara komprehensif, baik dalam kajian tafsir, hadis, dan fiqh, maupun dalam praktik kurikulum di PTKIN dan sekolah berbasis Islam. Tantangan yang muncul meliputi resistensi dari kalangan konservatif, keterbatasan sumber daya akademik, serta konflik metodologis antar disiplin. Kebaruan penelitian ini terletak pada sintesis teori interdisipliner Nissani, paradigma integrasi-interkoneksi Amin Abdullah, dan konsep kolaborasi epistemik Miller yang menegaskan interdisipliner bukan sekadar pilihan metodologis, melainkan paradigma strategis dalam membangun studi Islam yang lebih dinamis, inklusif, dan solutif.